FACTORS THAT CAUSE FEELINGS OF LONELINESS IN ADOLESCENTS (Academia Science Repository, 2023)
From the psychological characteristics characteristic of adolescence in this article one is the problem of loneliness in husus, as well as the self-awareness of the individual research on trends and factors affecting it the results were reviewed in hususu.